A Sociological Reconstruction of Memory, The case of Iranian Exile - Vahabi, Nader (Cultural and religious studies, 2015)
It has been 36 years since exiled Iranians who were eliminated from society in Iran settled in Europe and in the world and found safety in exile. How can we assess their memory? How does memory construct and modify over the course of time? How can life trajectories and social processes affect and transform their memory? The response to these questions inevitably leads us towards an analysis of the social dynamics of memory. What we have to contend with is not just a simple recording of memories pulled from oral histories. Our research is mainly centered on a sociological analysis of memory. This paper locates itself at a crossroads between two methodologies: The first has been gleaned from E. Goffman’s concept of "moral career" and the second is heavily inspired by M. Halbwach’s sociology where: New social frameworks shatter memory. For this reason, the supposed "collective" and "homogenous" memory, forged during the Iranian revolution of 1979 and shown to be ultimately subjective, cannot be conserved intact in exile. In point of fact, memory breaks down progressively when the social frameworks for individual resocialization exploit different places of exile. Memory then transforms itself with due respect to the new social environments, and this is a specific feature of the life trajectories of those exiled. This paper is a result of our research on the subjectivity of 200 Iranian political migrants carried out since our thesis in 2003 in seven countries, Turkey (Istanbul), France (Paris, Toulouse, Montpellier), Germany (Cologne), England (London), Hungry (Budapest), Austria (Vienna).